The suitability of Sanders` model for calculation of the propulsive force generated by the hands during sculling motion - Gomes, L. E.; Boeira, L.; Fagundes Loss, J. (Journal of Sports Sciences, 2017)
This study examined whether Sanders` model is suitable for estimating accurately the propulsive force generated by the hands` motion in swimming comparing the calculated force obtained using the model and the measured force during an actual propulsive action. The measured and calculated forces were obtained from 13 swimmers who, while tethered, performed a sculling motion in a prone position for the purpose of displacing the body by moving it forward. Kinematic analyses were conducted to obtain the calculated force, while the measured force was obtained via the use of a load cell. The calculated force was lower than the measured force and accounted for only a small part of the variation in the measured force. The forces could not be used interchangeably, and there were fixed and proportional differences between them. Consequently, this study indicates that Sanders` model is not suitable for estimating accurately the propulsive force generated by the swimmer`s hands during sculling motion. However, research that integrates analyses from different approaches could result in improvements to the model that would render it applicable for estimating the propulsive forces during movements that are characterised by directional changes of the hands.